2016
DOI: 10.1097/j.pain.0000000000000351
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of acute low back pain

Abstract: Characterising the clinical course of back pain by mean pain scores over time may not adequately reflect the complexity of the clinical course of acute low back pain. We analysed pain scores over 12 weeks for 1585 patients with acute low back pain presenting to primary care to identify distinct pain trajectory groups and baseline patient characteristics associated with membership of each cluster. This was a secondary analysis of the PACE trial that evaluated paracetamol for acute low back pain. Latent class gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 50 publications
4
56
0
1
Order By: Relevance
“…The clinical course for leg pain and disability was favourable for all four clusters, with most improvement seen in the first 3 months. This early improvement is confirmed in other sciatica trajectory studies and is also seen in cohorts with non-specific low back pain (Axen & Leboeuf-Yde, 2013;Downie et al, 2016). An interesting observation is the early improvement in pain and disability across the four clusters despite approximately two of three patients in all clusters having their pain for over 3 months.…”
Section: Discussionsupporting
confidence: 75%
“…The clinical course for leg pain and disability was favourable for all four clusters, with most improvement seen in the first 3 months. This early improvement is confirmed in other sciatica trajectory studies and is also seen in cohorts with non-specific low back pain (Axen & Leboeuf-Yde, 2013;Downie et al, 2016). An interesting observation is the early improvement in pain and disability across the four clusters despite approximately two of three patients in all clusters having their pain for over 3 months.…”
Section: Discussionsupporting
confidence: 75%
“…To our knowledge, LBP trajectories in adults have so far been identified by data driven approaches in ten cohorts [ 8 , 10 18 ]. In these studies, participants with a main complaint of LBP were followed from three to twelve months with data collection at four to 52 time-points.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all studies identified patterns that were neither a rapid recovery nor persistent severe pain. Different patterns of improvement in the very early course were mainly observed in the studies that included many patients with recent onset pain [ 11 , 12 , 18 ]. In addition, most studies described fluctuating patterns characterised by LBP of alternating intensity and/or by LBP episodes with periods of no pain.…”
Section: Discussionmentioning
confidence: 99%
“…Growth curve modeling has been previously applied to describe patterns of recovery over weeks in patients with acute low back pain [5] and over days in hospitalized medical and surgical patients [10]. Patterns of pain resolution in the first 5-6 5-6 postoperative days have been described and correlated with persistent pain months later [1; 4; 14], yet the few studies which have modeled these patterns have been restricted to short time periods (two weeks) [3] or included a paucity (≤ 6) measures [11; 13; 15; 16].…”
Section: Introductionmentioning
confidence: 99%